Workshop Pembuatan Laporan Keuangan Dasar Organisasi Nirlaba untuk Santri Lembaga Kesejahteraan Sosial Anak (LKSA) Nurul Iman - Dede Mustomi; Asep Dony Suhendra; Khoirul Ulum; Maria Lapriska Dian Ela Revita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
ABSTRACT Financial reports for an organization are very fundamental. This is a form of transparency for the finances of an organization, especially for non-profit organizations such as the Child Social Welfare Institution (LKSA Nurul Iman) which is a community service partner this time. We from the Business Administration Study Program, Faculty of Economics and Business, Bina Sarana Informatika University held a community service with the main theme being a Workshop on Making Basic Financial Reports for Non-Profit Organizations for Students of the Child Welfare Institution (LKSA Nurul Iman). The main problem why we raised this theme is because LKSA Nurul Iman touches more on programs that are religious in nature, even though the challenges ahead are more difficult and global so that teenagers who are currently studying must be given general knowledge, one of which is understanding financial reporting. Departing from these problems, we provide a solution in the form of a financial report preparation workshop, where we will describe the steps for making financial reports that are easily understood by their age. The method we use in community service this time is in the form of a workshop by providing examples of how to make basic financial reports and immediately put them into practice so that participants can absorb the material provided. The implementation of community service this time is still online using the Zoom application. The use of the Zoom application is due to the pandemic that has not ended and is still PPKM level 2. The output achieved in this community service is in the form of a Press Release which will be published in online media. Hopefully this activity will have a positive impact where the skills gained can be used in the future for the benefit of the Foundation and become provisions when they apply for jobs or establish an organization.